Methicillin‐resistant Staphylococcus aureus among elderly patients with community-acquired pneumonia. Issue 8 (August 2022) - Goto, Akihiko; Komiya, Kosaku; Yamasue, Mari; Yoshikawa, Hiroki; Umeki, Kenji; Hiramatsu, Kazufumi; Kadota, Jun-ichi
Abstract: Introduction: The 2019 American Thoracic Society/Infectious Diseases Society of America guidelines for community-acquired pneumonia (CAP) recommend methicillin‐resistant Staphylococcus aureus (MRSA) coverage for patients with prior sputum isolation of MRSA. This study aimed to determine the impact of MRSA coverage on in-hospital mortality in elderly patients with CAP among whom MRSA was isolated. Methods: Consecutive elderly patients who were admitted for CAP and had positive sputum culture for MRSA were retrospectively included, and the association between MRSA coverage and in-hospital mortality was analyzed. Results: Twenty (18%) of 111 patients received MRSA coverage. Although patients who received MRSA coverage tended to have more frequent prior isolation of MRSA compared to those who did not, no significant difference in in-hospital mortality was observed between both groups (2/20, 10% vs. 8/91, 9%). MRSA coverage was not associated with in-hospital mortality (odds ratio: 1.15; 95% CI: 0.23–5.89, p = 0.864); however, advanced age, hemoglobin level, a high A-DROP score, and C-reactive protein levels were associated with in-hospital mortality. MRSA coverage may not improve the prognosis of elderly patients with CAP who had positive sputum culture for MRSA. Conclusions: A randomized control study is required to determine the efficacy of MRSA coverage on the management of CAP in elderly patients.